Nuptials At Vespers And Other Strains - Ngong Kum Ngong, John (Book collections on Project MUSE., 2015)
Another exciting and confrontational poetry collection by the award-winning poet, John Ngong Kum Ngong. Nuptials At Vespers And Other Strains is his eighth collection of 44 poems. These poems particularly handle questions of identity, delineating the poet-persona's struggle to detach himself from the bard and be like any ordinary person in society. After a bootless tussle and a depression, he makes friends with the poet .Together they view their situation as a marriage and a prison full of pain, torture and suffering. They desire to end their affliction fighting together. There is a hint of regret, disappointment and even bitterness but the prevailing mood of love and concern spell hope in darkness.